1997
DOI: 10.1152/ajpgi.1997.273.2.g553
|View full text |Cite
|
Sign up to set email alerts
|

Survival of human pancreatic enzymes during small bowel transit: effect of nutrients, bile acids, and enzymes

Abstract: The activity of pancreatic enzymes declines during aboral intestinal transit. We tested the hypothesis that survival of pancreatic enzyme activities during intestinal transit is affected by amounts or concentrations of calories, nutrients, bile acids, or pancreatic enzymes entering the segments of the small intestine. An oroileal tube was placed in 26 healthy humans. The tube had duodenal, jejunal, and ileal infusion ports for nonabsorbable markers and aspiration ports in the distal duodenum, distal jejunum, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
3

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 11 publications
1
29
0
3
Order By: Relevance
“…Evidence in humans suggests that the pancreatic response to a meal is regulated by the rate of nutrient delivery (17). In addition, Holtmann et al (12) showed an inverse relationship between small intestinal transit and pancreatic lipase activity. An accelerated transit of the nutrient meal, through the stimulation of small intestinal burst activity, may have blunted the pancreatic response and could explain the diminution of lipid uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence in humans suggests that the pancreatic response to a meal is regulated by the rate of nutrient delivery (17). In addition, Holtmann et al (12) showed an inverse relationship between small intestinal transit and pancreatic lipase activity. An accelerated transit of the nutrient meal, through the stimulation of small intestinal burst activity, may have blunted the pancreatic response and could explain the diminution of lipid uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which CDL activity is destroyed lies on chymotrypsin-catalyzed proteolysis. Less than 1% of the lipolytic activity secreted into the duodenum reaches the ileum as compared to 22% for the trypsin activity (Holtmann et al, 1997). As for CDL, BSDL could be extremely sensitive to proteolysis and easily degraded by chymotrypsin.…”
Section: Discussionmentioning
confidence: 99%
“…The rates of degradation, however, differ from one enzyme to the other (Holtmann et al, 1997). In what concerns CDL, its activity decreases rapidly in contrast to proteases and amylases, which are relatively more stable.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 In addition, in the acidic duodenal milieu, bile salt precipitation and subsequent adsorption to undigested food reduces the bile salt pool. 4,5 And finally, CP patients are believed to have a defect in ileal mucosal absorption of bile salts, effectively reducing the availability of bile salts for enterohepatic circulation.…”
Section: Dovepressmentioning
confidence: 99%